2018
DOI: 10.1111/ijcp.13240
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hypoglycaemia in people aged ≥65 years receiving linagliptin: pooled data from 1489 individuals with type 2 diabetes mellitus

Abstract: This pooled analysis indicates that linagliptin was effective in treating older people with T2DM towards their HbA1c targets with a favourable safety and tolerability profile and low risk of hypoglycaemia. The safety profile was maintained even on background therapies with known risk of hypoglycaemia, such as insulin and SU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Previous studies investigating the safety and efficacy of linagliptin in older patients found that linagliptin provided effective glucose control in this population, without a significant increase in undesirable AEs . Importantly, linagliptin did not increase the risk of hypoglycaemia in older patients even when used in conjunction with therapies with a known risk of hypoglycaemia, such as insulin and sulphonylureas …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies investigating the safety and efficacy of linagliptin in older patients found that linagliptin provided effective glucose control in this population, without a significant increase in undesirable AEs . Importantly, linagliptin did not increase the risk of hypoglycaemia in older patients even when used in conjunction with therapies with a known risk of hypoglycaemia, such as insulin and sulphonylureas …”
Section: Discussionmentioning
confidence: 89%
“…19,21 Importantly, linagliptin did not increase the risk of hypoglycaemia in older patients even when used in conjunction with therapies with a known risk of hypoglycaemia, such as insulin and sulphonylureas. [19][20][21] We recognize limitations to this study. The lower age cut-off for study inclusion was reduced to 60 years through a protocol amendment, while guideline-based thresholds for "elderly" populations refer to either 65 or 70 years of age, respectively.…”
Section: Overall Safetymentioning
confidence: 92%
See 2 more Smart Citations
“…Linagliptin is a glucose-lowering drug with a good safety profile established across multiple clinical trials [11]. Meta-analyses that included data from participants aged ≥ 65 years have confirmed that the safety profile of linagliptin also extends to its use in the elderly population [28, 29]. In the current study conducted in Japanese older patients, linagliptin was well tolerated, and AEs occurred with similar rates in both the linagliptin and placebo groups.…”
Section: Discussionmentioning
confidence: 52%